The perception of students of unioeste executive secretariat on the applicability of Design thinking - Gregolin, Lilian Antunes; Vigorena, Debora Liessem (Seven Editora, 2023)
Faced with a competitive market, many organizations seek to adopt methodologies and tools that promote innovation in order to obtain constant growth and ensure their position in the market. In this scenario, design thinking (DT) presents itself as an accessible and effective methodology to implement innovative ideas. Therefore, it is relevant for the secretarial professional, who is inserted in a competitive labor market, to improve and master innovative methodologies. Thus, this study aims to evaluate the perception of Unioeste Executive Secretariat students who attended the discipline of Innovation Management (2020), regarding the fundamentals of design thinking and its applicability. To this end, a semi-structured interview was conducted with nine questions on the subject to the graduates of the discipline. Through the results, it was found that the students understood the fundamentals of the approach and consider it relevant for their professional growth. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-166